STUDY OF GELATIN FROM DUCK BONE AS AN ALTERNATIVE SOURCES OF HALAL GELATIN - Muhammad Habbib Khirzin (JURNAL SAINS NATURAL, 2020)
Gelatin is an intermediate ingredient which is oftenly used in many field such as food, pharmacy, and cosmetics. It is usually extracted from pig and cow. Halal issue of gelatin sources and the outbreaks of mad cow diseases encouraged people to find an alternative sources of gelatin. One of the alternative sources of gelatin was duck bone. The aim of this research was to describe physicochemical properties of duck bone gelatin which is extracted by using acid extraction method as an alternative sources of halal gelatin. The extraction of duck bone gelatin used 5% concentration of HCl (hydrochloric acid). The extraction process consisted of four steps, they were degreassing, defating, demineralization, and acid extraction. The result showed that gelatin which was extracted from duck bone had these several characteristic: yield of 6.24%, pH 4.0, water content of 13.43%, ash content of 13.42%, protein content of 65.43%, and whiteness degree of 30.35%. Generally, gelatin which was extracted from duck bone had similar characteristic with commercial gelatin and SNI standard. Further researcher had been suggested to reoptimized extraction method in order to reduce ash content.